2021
DOI: 10.3390/nu13072147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Immunonutrition on Postoperative Major Morbidity after Cytoreductive Surgery and HIPEC in Patients with Peritoneal Metastasis

Abstract: The effect of preoperative immunonutrition intake on postoperative major complications in patients following cytoreductive surgery (CRS) with or without hyperthermic intraperitoneal chemotherapy (HIPEC) was assessed. The accuracy of C-Reactive Protein (CRP) for detecting postoperative complications was also analyzed. Patients treated within a peritoneal carcinomatosis program in which a complete or optimal cytoreduction was achieved were retrospectively analyzed. They were divided into two groups based on whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…As chemotherapy is an integral part of ovarian cancer management, a delay in adjuvant treatment beyond 25 to 35 days due to surgical morbidity will result in a significantly poorer prognosis [29]. Other studies, however, failed to demonstrate such Candela et al reported significant differences in baseline characteristics between intervention and control groups [30]. All studies clearly described the prehabilitation interventions administered to patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As chemotherapy is an integral part of ovarian cancer management, a delay in adjuvant treatment beyond 25 to 35 days due to surgical morbidity will result in a significantly poorer prognosis [29]. Other studies, however, failed to demonstrate such Candela et al reported significant differences in baseline characteristics between intervention and control groups [30]. All studies clearly described the prehabilitation interventions administered to patients.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these programmes are multimodal, comprising exercise therapy, nutritional guidance, psychological interventions and treatment of intoxications and anaemia, with exercise being one of the most important mainstays [21,34]. A recent systematic review and metaanalysis comprising 3962 patients undergoing abdominal cancer surgery found Candela et al reported significant d intervention and control groups [30]. A interventions administered to patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations